2018
DOI: 10.1002/ece3.4407
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen enrichment alters nutrient resorption and exacerbates phosphorus limitation in the desert shrub Artemisia ordosica

Abstract: Increasing nitrogen (N) deposition and precipitation are major drivers of global changes that are expected to influence plant nutrient resorption in desert ecosystems, where plant growth is often nutrient and water limited. However, knowledge on the effects of increased N and precipitation on them remain poorly understood. This study determined the effects of increased N (ambient, 60 kg N ha−1 year−1) and water supply (ambient, +20%, +40%), and their combination on the leaf nutrient resorption of Artemisia ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Both low and high P addition increased seed production in the presence of N addition, and the increment was significantly higher under high N addition than under low N addition, indicating that a P limitation of seed production can be triggered by N addition. This phenomenon is supported by model simulation work (Menge & Field, 2007) as well several field experiments (Marklein & Houlton, 2012; Zheng et al, 2018). Plants capable of a high growth rate under N‐rich conditions will require a greater allocation of P‐rich rRNA to support macromolecular (protein, rRNA) synthesis (Niklas et al, 2005).…”
Section: Discussionsupporting
confidence: 52%
“…Both low and high P addition increased seed production in the presence of N addition, and the increment was significantly higher under high N addition than under low N addition, indicating that a P limitation of seed production can be triggered by N addition. This phenomenon is supported by model simulation work (Menge & Field, 2007) as well several field experiments (Marklein & Houlton, 2012; Zheng et al, 2018). Plants capable of a high growth rate under N‐rich conditions will require a greater allocation of P‐rich rRNA to support macromolecular (protein, rRNA) synthesis (Niklas et al, 2005).…”
Section: Discussionsupporting
confidence: 52%
“…Both low and high P addition increased seed production in the presence of N addition, and the increment was significantly higher under high N addition than under low N addition, indicating that a P limitation of seed production can be triggered by N addition. This phenomenon is supported by model simulation work (Menge & Field, 2007) as well several field experiments (Marklein & Houlton, 2012;Zheng et al, 2018). Plants capable of a high growth rate under N-rich conditions will require a greater allocation of P-rich rRNA to support macromolecular (protein, rRNA) synthesis (Niklas et al, 2005).…”
Section: Impact Of P Addition On Seed Productionmentioning
confidence: 81%
“…A previous study also showed that the PRE of one grass species decreased while that of another increased with increasing SAP (Li, Gao, et al, 2016). However, Zheng et al (2018) found no significant relationship between PRE and SAP. These remarkably different responses may be related to the soil nutrient status or species‐specific responses of leaf PRE to SAP (Huang et al, 2012; Li, Gao, et al, 2016; Lü et al, 2013; Lü & Han, 2010; Zhang, Tang, et al, 2015; Zheng et al, 2018; Zong et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Nutrient resorption is correlated with climate, tissue chemistry, and soil biology (Killingbeck, 1996; Ren et al, 2015; Yuan & Chen, 2009), all of which can be driven by N deposition (Wang et al, 2014; Zhang, Li, et al, 2015; Zheng et al, 2018). Increased use of fertilizers and enhanced N deposition have significantly increased soil nutrient availabilities (Bobbink et al, 2010; Galloway et al, 2004; Zhang, Li, et al, 2015) and leaf nutrient concentrations and thus influence the nutrient resorption patterns of plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation